Occurrence of Salmonella spp. in chicken carcasses commercialized in open markets in the city of Manaus - Amazonas - Tirolli, Izabel Cristina Campos; Costa, Cristóvão Alves da (Acta Amazonica, 2006)
This research evaluates the levels of salmonella that are present in chicken carcasses commercialized in shops and public markets in different zones in the city of Manaus, Amazonas - Brazil. Sixty samples were randomly collected in a period of eleven weeks and examined specifically for Salmonella presence. Fifty percent of the samples were positive for Salmonella, and 67 serovars were isolated and distributed mainly among 11 different sorotypes. Those identified, S. panama, S. mbandaka, S. schwarzengrund, S. typhimurium, S. albany, S. agona, corresponded to 85%. The contamination of Salmonella is dependent on various factors, and its occurrence may berelated to the hygeine conditions of the poultry farm. The methodology used for the microbiological detection was that recommende by the "Food and Drugs Administration" of the United States of America.
Ocorrência de Salmonella spp. em carcaças de frangos recém abatidos em feiras e mercados da cidade de Manaus-AM
Keywords: Salmonella; Salmonella Typhimurium